A Qualitative Investigation into the Awareness and Effectiveness of Social Health Insurance in Ward No. 8, Chandragiri Municipality, Kathmandu District, Nepal - Bishnu Raj Kafle; Dr. Vijesh Kumar (Journal of Development Review, 2025)
This study aims to investigate the level of understanding, accessibility, and use of the Social Health Insurance (SHI) program in Chandragiri Municipality. Kathmandu District, specifically in Ward No. 8. Focus group discussions with community members were held in addition to interviews with fifteen people, five local leaders, five healthcare providers, and a qualitative case The research method was applied. The SHI program is still not widely known, and there were significant gaps in understanding regarding what it offers, how to apply, and how to make use of it. Furthermore, people’s opinions SHI program’s awareness and effectiveness were mixed or neutral. These findings align with international research suggesting comparable issues impacting the SHI’s effectiveness in rural and low-income communities. The study presents various interventions that could potentially address the challenges mentioned. However, it ultimately concludes that the issue can only be resolved by establishing extensive networks of participating clinics, providing more funding, streamlining paperwork, and developing effective advertising campaigns that target the specific obstacles faced by the patient population. To improve SHI utilization, planned communication activities that take into account the targeted population’s demographic and socioeconomic characteristics are recommended. By using awareness efforts that will improve the SHI program, stakeholders can alter perspectives and close the knowledge gap. The Chandragiri Municipality’s SHI program may serve as a model for improving financial risk protection and healthcare access in other low-income environments across the world by tackling these problems.